Post Larvae Tolerance of Vaname Shrimp Under Salinity Stress With Spirullina Sp. Extract Supplementation: A Meta-Analysis Approach - Prameswary, Innes; Mardani, Oktantia Almira Putri; Taqiya, Rakhesa Izzah; Rabani, Wigar; Rusdi; Lisanti, Elsa; Lisanti , Elsa (Jurnal Media Akuakultur Indonesia, 2024)
Vaname shrimp (Litopenaeus vannamei) is one of Indonesia's fishery commodities with high economic value. In order to successfully cultivate vaname shrimp, it is important to consider the survival of shrimp during the post larval phase because it is one of the most crucial phases in shrimp survival. This article aims to determine the feeding of Spirulina sp. extract during the post larval period of vaname shrimp to increase the tolerance potential of salinity stress. This research uses a meta-analysis method by searching previous journals that are relevant with the topic of discussion. Furthermore, the articles that have been obtained are analyzed to form a discussion and conclusion. The results of the analysis shows the utilization of Spirulina sp. extract as an additional feed has a positive and significant effect on the weight gain and survival rate of vaname shrimp due the salinity stress. Significant results began to appear at 0.4% concentration of Spirulina and progressively increased as its concentration increased. However, the use of concentrations of Spirulina too much or too low showed a decreasing trend. These results indicate that Spirulina sp. can potentially be used as an additional feed for vaname shrimp